Gastrointestinal Factors Associated With Hospitalization in Infants With Cystic Fibrosis: Results From the Baby Observational and Nutrition Study. Issue 3 (18th September 2021) - Sathe, Meghana; Huang, Rong; Heltshe, Sonya; Eng, Alexander; Borenstein, Elhanan; Miller, Samuel I.; Hoffman, Lucas; Gelfond, Daniel; Leung, Daniel H.; Borowitz, Drucy; Ramsey, Bonnie; Freeman, A. Jay
ABSTRACT: Objectives: To identify factors that increase the risk of gastrointestinal-related (GI-related) hospitalization of infants with cystic fibrosis (CF) during the first year of life. Methods: The Baby Observational and Nutrition Study was a longitudinal, observational cohort of 231 infants diagnosed with CF by newborn screening. We performed a post-hoc assessment of the frequency and indications for GI-related admissions during the first year of life. Results: Sixty-five participants had at least one admission in the first 12 months of life. High pancreatic enzyme replacement therapy (PERT) dosing (>2000 lipase units/kg per meal; hazard ratio [HR] = 14.75, P  = 0.0005) and use of acid suppressive medications (HR = 4.94, P  = 0.01) during the study period were positively associated with subsequent GI-related admissions. High levels of fecal calprotectin (fCP) (>200 μg/g) and higher relative abundance of fecal Klebsiella pneumoniae were also positively associated with subsequent GI-related admissions (HR = 2.64, P  = 0.033 and HR = 4.49, P  = 0.002, respectively). During the first 12 months of life, participants with any admission had lower weight-for-length z scores (WLZ) ( P  = 0.01). The impact of admission on WLZ was particularly evident in participants with a GI-related admission ( P  < 0.0001). Conclusions: Factors associated with a higher risk for GI-related admission during the first 12 months include high PERT dosing, exposure to acid suppressive medications, higher fCP levels, and/or relative abundance of fecal K pneumoniae early in life. Infants with CF requiring GI-related hospitalization had lower WLZ at 12 months of age than those not admitted as well as those admitted for non-GI-related indications.